Analisis Metode Penerjemahan Bahasa Arab Dalam Film Kartun: “Ibnu Sina” - Al Hasan, Mutiah; novita ratnawati, Yuli; edidarmo, Toto (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2024)
The purpose of this study is to understand and explain the translation method used in the process of translating Arabic cartoon movies from Arabic into Indonesian. The theory of translation method used is Peter Newmark's theory of translation method. The researcher used the descriptive method of qualitative research. The listening method and note-taking technique were used for data collection. The data source of this research is taken from the subtitles of Arabic animated cartoon film: Ibn Sina on Sukardi Hasanudin's youtube channel episode 1 (one). The data obtained in the form of 89 data were researched and analyzed. The result of the analysis found 7 translation methods applied by the translator in the Arabic cartoon film: Ibnu Sina, namely word-for-word translation of 32 data (36%), literal translation of 4 data (4%), faithful translation of 10 data (10%), semantic translation of 5 data (5%), free translation of 23 data (26%), idiomatic translation of 1 data (1%), communicative translation of 14 data (16%). The dominant translation methods used are word-for-word translation and free translation.